Perancangan Alat Pencetak Kulit Dimsum yang Ergonomis Pada UD. Soponyono - Helda, Helda Prisdana Hardinta; Handy Febri Satoto (Jurnal Serambi Engineering, 2025)
UD. Soponyono is a business group operating in the food sector. The process of making dimsum skin takes 2.5. Soponyono produces up to 100 kg of dim sum skin every day with a working time of 8 hours per day. Good working posture can support worker comfort and reduce the risk of injury. In this research, measurements were carried out using anthropometric and percentile approaches to determine worker dimensions. This approach aims to obtain accurate data regarding variations in workers' body sizes, so that the results can be used to design ergonomic tools or work facilities. The resulting data includes various worker body parameters, which are then analyzed to ensure compliance with design requirements and occupational safety standards. The dimensions used for the design are vertebral height 84.50 cm, shoulder width 45.58 cm, upper arm length 35.03 cm, and forward arm span 74.26 cm. To operate this tool, press the handle of the tool and then press it down to make the printing process easier.